SUBSURFACE INTERPRETATION OF GEOTHERMAL MANIFESTATIONS KARANGREJO VILLAGE ARJOSARI SUBDISTRICT, PACITAN WITH GEOMAGMETIC METHOD - Lestari Tri Eva; Darmawan Denny; Wibowo Nugroho Budi (Jurnal Ilmu Fisika dan Terapannya (JIFTA), 2016)
The goal is to find out the distribution of the residual anomaly of magnetic field and identification of subsurface and cap rock geothermal manifestation in Karangrejo. Data collection was carried out during 3 days with spacing between points were 500 m and 100 m using Precision Proton Magnetometer (PPM). Data processing was done with diurnal correction, IGRF correction, topography correction, reduction to the pole and upward continuation. Interpretation process of the data was done by analyzing the local anomaly that has been done to the reduction to the pole and upward continuation to a height of 300 m which has been modeled using Mag2DC software. Interpretation results show that the value of local anomaly magnetic field to the pole is -600 nT to 100 nT while interpretation of the results of 2 slices model indicate het domination of lava rock and breccia rock